N-p co-doped-zincophilic layer composite modified zinc-bromine flow battery carbon felt, and preparation method and application thereof
Patent Information
- Application Number
- CN202611477475.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-10-30
AI Technical Summary
但是,其热量大量消耗于碳纤维表层的氧化性烧蚀、长保温热损失与重复升降温过程,单位面积碳毡的电耗更高,且能耗并未转化为可控掺杂或强锚定界面,反而导致碳毡纤维本体脆化风险;同时,所形成的活性层来源于浸盐-热转化,而非在可控活性位点上的原位咬合生长,界面锚定力弱,在锌沉积/溶解往复与液流冲刷下易于发生局部剥落、颗粒粗化与枝晶诱发,直接导致锌溴液流电池的电池容量、库伦效率的持续衰减,限制电池的长期循环性能
(1)本发明通过N-P共掺杂方式对碳毡基体进行电子结构改性,可同步提升电极的导电性、电催化活性、亲水性及电解液耐蚀稳定性:由于N原子电负性大于碳原子,可有效调控碳纤维表面电子分布,使相邻碳原子呈现部分正电性,大幅增加碳毡表面对锌离子的吸附活性位点,显著降低锌沉积/剥离反应的能垒与反应过电位,加快电极表面氧化还原反应动力学,有效提升层内导电性能与电催化活性;另外,由于P原子半径较大,掺杂后可形成稳定的P-C、P-O-C化学键结构,撑开碳材料微晶层间距,增大比表面积,显著改善碳毡表面亲水性与电解液浸润能力;同时,P-C、P-O-C结构具备优异的耐酸性与耐溴氧化性,能够有效抑制碳基体被电解液中溴单质腐蚀,大幅提升电极结构稳定性。此外,N、P二者形成电子效应互补的协同调控机制,使碳毡表面电荷分布更加均匀,显著提升锌成核密度,有效避免锌离子局部富集与择优生长,从反应根源上抑制了尖锐锌枝晶的生成,实现锌沉积的均匀化,解除锌枝晶生成的外部环境条件。
Smart Images

Figure CN123018001A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of zinc-bromine flow battery materials technology, and in particular to an NP co-doped zinc-loving layer composite modified zinc-bromine flow battery carbon felt, its preparation method and application. Background Technology
[0002] Zinc-bromine flow batteries have become a preferred technology for large-scale energy storage due to their low cost, high safety, and moderate energy density. The zinc affinity, electrocatalytic activity, conductivity, and stability of the carbon felt electrode are key performance factors. Currently, the carbon felt electrode used in zinc-bromine flow batteries suffers from zinc dendrite growth, which can easily puncture the separator, leading to short circuits and battery failure, posing a safety hazard. To address this issue, existing technologies mainly use heavy metals to modify the carbon felt, but this still suffers from the following major technical challenges: while traditional metal (Pb, Cu)-modified carbon felt can improve its zinc affinity, the metals are prone to leaching and agglomeration, resulting in poor long-term cycle stability of the carbon felt electrode. Furthermore, the leached heavy metals can cause environmental pollution, failing to meet the needs of green energy storage development and making it unsuitable for large-scale applications.
[0003] Existing technologies disclose techniques for electrodepositing elemental tin on the surface of carbon felt using a slightly alkaline electrolyte to form a zinc-loving interface layer; however, the electrodeposited metallic Sn in Br2 / Br - The system is subject to risks of interface transformation and component migration, and electrodeposition tends to preferentially block pores on the surface of the three-dimensional thick felt, making it difficult to balance zinc affinity and mass transfer channels. At the same time, the carbon felt prepared by this method cannot effectively suppress the formation of sharp zinc dendrites, making it impossible to achieve long-cycle efficiency.
[0004] Chinese patent document CN117832517A discloses a zinc-bromine flow battery negative electrode material, its preparation method, and the zinc-bromine flow battery itself. The method employs a high-temperature heat treatment to load metal oxides such as nickel / cobalt / tin onto the surface of a carbon felt. Specifically, the carbon felt is first subjected to high-temperature pre-oxidation in air to obtain a rough, oxygen-containing surface. Then, it is impregnated with a solution of organometallic acid salts such as nickel / cobalt / tin and undergoes a second high-temperature thermal conversion, thereby obtaining a single metal oxide layer such as NiO, Co3O4, or SnO2 on the fiber surface. The long-term high-temperature pre-oxidation in air is solely for obtaining a rough, oxygen-containing surface; the subsequent second high-temperature calcination achieves the conversion of the organometallic acid salts into single metal oxides. However, a large amount of its heat is consumed by oxidative ablation of the carbon fiber surface, heat loss during long insulation, and repeated heating and cooling processes, resulting in higher power consumption per unit area of carbon felt. Moreover, the energy consumption is not converted into controllable doping or strong anchoring interface, but instead leads to the risk of embrittlement of the carbon felt fiber itself. At the same time, the active layer formed is derived from salt immersion-thermal conversion, rather than in-situ interlocking growth on controllable active sites. The interface anchoring force is weak, and it is prone to local peeling, particle coarsening, and dendrite induction under the repeated zinc deposition / dissolution and liquid flow scouring. This directly leads to the continuous decay of the battery capacity and coulombic efficiency of the zinc-bromine flow battery, limiting the long-term cycle performance of the battery.
[0005] Based on this, to address the problems of heavy metal leaching, interfacial instability, high energy consumption in high-temperature preparation of metal oxides, carbon felt fiber embrittlement, and easy peeling of the active layer in existing modified carbon felts, a green, efficient, and stable composite modified carbon felt was developed. While achieving synergistic improvement in zinc affinity, interfacial bonding, catalytic activity, and long-term stability, it effectively suppresses zinc dendrites and effectively improves the battery capacity, coulombic efficiency, and long-term cycle life of zinc-bromine flow batteries using this carbon felt, meeting the needs of large-scale energy storage applications and becoming the key to solving the long-cycle bottleneck of zinc-bromine flow batteries. Summary of the Invention
[0006] To address the technical problems existing in the prior art, this invention provides a method for preparing an NP co-doped zinc-loving layer composite modified carbon felt for zinc-bromine flow batteries. While achieving a synergistic improvement in zinc affinity, interfacial bonding, catalytic activity, and long-term stability, it effectively suppresses zinc dendrites and effectively improves the battery capacity, coulombic efficiency, and long-term cycle life of zinc-bromine flow batteries using this carbon felt, thus meeting the needs of large-scale energy storage applications.
[0007] The present invention also provides an NP co-doped zinc-loving layer composite modified zinc-bromine flow battery carbon felt prepared by the same method.
[0008] The present invention also provides the application of the NP co-doped-zincophilic layer composite modified zinc bromine flow battery carbon felt.
[0009] To solve the above technical problems, the technical solution adopted by the present invention is as follows: A method for preparing NP co-doped zinc-loving layer composite modified carbon felt for zinc-bromine flow batteries includes the following steps: Step S01: The carbon felt is washed and dried to obtain pretreated carbon felt; Step S02: Place the pretreated carbon felt in the precursor solution, ultrasonically impregnate it, take it out and dry it; then heat it to 450~550℃ under an inert atmosphere and keep it at the temperature for calcination to obtain NP co-doped carbon felt. The precursor solution is an aqueous solution of ammonium dihydrogen phosphate in which chitin is dispersed. Step S03: Place the NP co-doped carbon felt in a mixed solution, ultrasonically impregnate it, remove it and dry it; then heat it to 300~400℃ in an oxygen atmosphere and keep it at the temperature for calcination to obtain the NP co-doped-zinc-loving layer composite modified zinc bromine flow battery carbon felt. The mixed solution is an aqueous solution of ethanol containing citric acid, SnCl4·5H2O, and ZrOCl2·8H2O.
[0010] Preferably, in step S02, the concentration of ammonium dihydrogen phosphate in the precursor solution is 0.25~0.3mol / L; the mass ratio of chitin to ammonium dihydrogen phosphate in the precursor solution is (1~5):1.
[0011] Preferably, in step S02, the mass ratio of chitin contained in the precursor solution to pretreated carbon felt is (1~25):1.
[0012] Preferably, in step S02, the inert atmosphere is one of the following: nitrogen, argon, helium, or neon; The heating rate to 450~550℃ is 2~6℃ / min; The calcination time is 2-6 hours.
[0013] Preferably, in step S03, the concentration of ZrOCl2·8H2O in the mixed solution is 0.1~0.2 mol / L; The mass ratio of SnCl4·5H2O to ZrOCl2·8H2O in the mixed solution is (1~5):1; The weight of citric acid added to the mixed solution is 5-10% of the total weight of SnCl4·5H2O and ZrOCl2·8H2O; The volume fraction of ethanol in the aqueous ethanol solution used in the mixed solution is 50-85%.
[0014] Preferably, in step S03, the mass ratio of ZrOCl2·8H2O to NP co-doped carbon felt in the mixed solution is (8.8~9.2):1.
[0015] Preferably, in step S03, the oxygen-containing atmosphere includes air; The heating rate to 300~400℃ is 1~5℃ / min; The calcination time is 1-5 hours.
[0016] Further, the method of step S01 is as follows: the carbon felt is washed sequentially with anhydrous acetone and anhydrous ethanol, then rinsed with deionized water; then placed in dilute nitric acid, kept at 70~80℃ for heat treatment, then rinsed with deionized water until neutral, and dried to obtain pretreated carbon felt.
[0017] A carbon felt for zinc-bromine flow batteries with NP co-doped zinc-loving layer composite modification is prepared using the aforementioned method.
[0018] A zinc-bromine flow battery employs the aforementioned NP co-doped zinc-loving layer composite modified zinc-bromine flow battery carbon felt.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The present invention modifies the electronic structure of the carbon felt matrix by NP co-doping, which can simultaneously improve the conductivity, electrocatalytic activity, hydrophilicity and electrolyte corrosion resistance of the electrode: Since the electronegativity of N atoms is greater than that of carbon atoms, the electron distribution on the carbon fiber surface can be effectively controlled, so that the adjacent carbon atoms are partially positively charged, which greatly increases the adsorption active sites for zinc ions on the carbon felt surface, significantly reduces the energy barrier and reaction overpotential of zinc deposition / stripping reaction, accelerates the redox reaction kinetics on the electrode surface, and effectively improves the conductivity and electrocatalytic activity within the layer; In addition, since the P atom has a large radius, it can form a stable PC and POC chemical bond structure after doping, which expands the interlayer spacing of carbon material microcrystals, increases the specific surface area, and significantly improves the hydrophilicity and electrolyte wetting ability of the carbon felt surface; At the same time, the PC and POC structure has excellent acid resistance and bromine oxidation resistance, which can effectively inhibit the corrosion of the carbon matrix by bromine in the electrolyte and greatly improve the stability of the electrode structure. Furthermore, the complementary electronic effects of N and P create a synergistic regulatory mechanism that makes the charge distribution on the carbon felt surface more uniform, significantly increases the zinc nucleation density, effectively avoids the local enrichment and preferential growth of zinc ions, inhibits the formation of sharp zinc dendrites from the root of the reaction, achieves uniform zinc deposition, and removes the external environmental conditions for zinc dendrite formation.
[0020] (2) This invention further solves key problems such as uneven zinc deposition, dendrite growth, and functional layer failure and shedding by constructing a SnO2-ZrO2 composite zinc-loving coating on the surface of NP co-doped carbon felt, thereby achieving a secondary enhancement of the zinc affinity of the electrode and long-cycle stability: by utilizing the characteristics of SnO2 and metallic zinc ions having similar radii and high lattice matching, a large number of uniform and stable zinc nucleation sites can be provided on the electrode surface, inducing uniform nucleation and planar growth of zinc ions; at the same time, SnO2 has moderate and uniform conductivity, which can avoid excessive local current density on the electrode surface, eliminate the tip enrichment effect, completely suppress the growth of zinc dendrites, and finally form a flat, dense, and defect-free zinc deposition layer, ensuring stable battery cycling. ZrO2 possesses excellent resistance to acid and bromine corrosion and high chemical stability. In composite coatings, it acts as a rigid skeleton support, effectively fixing the SnO2 active component and preventing SnO2 from dissolving, migrating, agglomerating, and falling off during long-term charge-discharge cycles. This maintains the integrity of the coating structure and its functional stability, continuously ensuring the electrode's uniform zinc affinity and dendrite suppression ability, and significantly extending electrode life and battery cycle life.
[0021] (3) This invention effectively solves the chain of uneven nucleation at the negative electrode interface - insufficient utilization within the pores - interface fatigue degradation - amplification of side reactions by synergistically combining NP co-doping with the SnO2-ZrO2 zinc-loving interface layer. Its working principle is as follows: by constructing a hierarchical structure of NP co-doped active framework + SnO2-ZrO2 zinc-loving interface layer on the carbon felt surface; wherein, NP co-doping introduces local charge polarization and defect active sites to improve surface wettability, electronic structure and Zn 2+ In the pre-adsorption field, SnO2 provides zinc-loving anchoring to reduce zinc nucleation overpotential and guide uniform deposition, while ZrO2 pins SnO2 particles with high chemical stability, inhibits their coarsening and exfoliation, and maintains the connectivity of three-dimensional channels. The two work together to change zinc deposition from concentrated growth at the tip to uniform nucleation at multiple sites and controllable filling along the framework, thereby simultaneously suppressing dendrites / dead zinc, slowing down hydrogen desorption side reactions, reducing polarization, and improving cycling stability.
[0022] (4) Compared with the heavy metal modification method, the calcination temperature in the NP doping (step SO2) process of this invention is 450~550℃, while the high-temperature shaping and sintering temperature (about 800℃) required by the heavy metal modification method is much lower, resulting in a reduction of more than 30% in overall energy consumption. At the same time, compared with the heavy metal modification method, this invention achieves comprehensive cost reduction in the preparation process by using inexpensive and readily available raw materials and a simple and continuous solution method of "immersion-calcination-coating", which significantly reduces the equipment investment and high energy consumption required by the heavy metal modification method. In terms of raw materials, readily available biomass chitin is used to replace expensive nitrogen-containing gases or chemical reagents, and an inexpensive SnO2-ZrO2 system is used to replace precious metal modification materials. In summary, this invention effectively reduces the manufacturing cost in large-scale production, and its total preparation cost is reduced by more than 30% compared with the existing heavy metal modification method, making it suitable for large-scale application of zinc-bromine flow battery energy storage power stations. Attached Figure Description
[0023] Figure 1 The constant current charge-discharge curves are used to test the electrochemical performance of the zinc-bromine flow battery using the NP co-doped zinc-philic layer composite modified carbon felt of Example 1 and the composite modified carbon felt of Comparative Example 1 as the negative electrodes of the zinc-bromine flow battery.
[0024] Figure 2 Cyclic curves are used to test the electrochemical performance of the zinc-bromine flow battery using the NP co-doped zinc-philic layer composite modified carbon felt from Example 1 as the negative electrode.
[0025] Figure 3 Cyclic curves are shown for electrochemical performance testing of the composite modified carbon felt used as the negative electrode in a zinc-bromine flow battery, as described in Comparative Example 1.
[0026] Figure 4 The image shows the X-ray diffraction (XRD) patterns of the NP co-doped zinc-loving layer composite modified zinc-bromine flow battery carbon felt of Example 1 and the pretreated carbon felt used therein.
[0027] Figure 5 This is a scanning electron microscope (SEM) image of the carbon felt of the NP co-doped zinc-loving layer composite modified zinc-bromine flow battery in Example 1.
[0028] Figure 6 The image shows a scanning electron microscope (SEM) image of the composite modified carbon felt in Comparative Example 1.
[0029] Figure 7 This is an electron image collected during energy-dispersive X-ray spectroscopy analysis of the NP co-doped-zincophilic layer composite modified zinc-bromine flow battery carbon felt of Example 1.
[0030] Figure 8 for Figure 7Energy-dispersive X-ray spectra (EDS) of the selected region (position 26). Detailed Implementation
[0031] To provide a clearer understanding of the technical features, objectives, and effects of this invention, specific embodiments are now described. It should be noted that the following detailed descriptions are exemplary and intended to provide further explanation of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0032] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the exemplary embodiments of the present invention. As used herein, "first," "second," etc., are used to distinguish similar objects and are not used to describe a particular order or sequence. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0033] In a first aspect, embodiments of the present invention provide a method for preparing an NP co-doped zinc-loving layer composite modified zinc-bromine flow battery carbon felt, comprising the following steps: Step S01: Cut the polyacrylonitrile (PAN)-based carbon felt to a suitable size, and then ultrasonically wash and dry it to obtain pretreated carbon felt; Step S02: Chitosan is dispersed in an aqueous solution of ammonium dihydrogen phosphate to obtain a precursor solution; the pretreated carbon felt is placed in the precursor solution, ultrasonically impregnated, removed and vacuum dried; then heated to 450~550℃ under an inert atmosphere and calcined to obtain NP co-doped carbon felt. Step S03: Dissolve citric acid, SnCl4·5H2O and ZrOCl2·8H2O in an aqueous ethanol solution to obtain a mixed solution; place the NP co-doped carbon felt in the mixed solution, ultrasonically impregnate it, remove it and vacuum dry it; then heat it to 300~400℃ in an oxygen atmosphere and calcine it to obtain the NP co-doped-zincophilic layer composite modified zinc bromine flow battery carbon felt.
[0034] In this embodiment of the invention, the electronic structure of the carbon felt matrix is modified by NP co-doping, which can simultaneously improve the conductivity, electrocatalytic activity, hydrophilicity, and electrolyte corrosion resistance of the electrode. Furthermore, N and P form a synergistic regulatory mechanism with complementary electronic effects, making the charge distribution on the carbon felt surface more uniform, significantly increasing the zinc nucleation density, effectively avoiding local enrichment and preferential growth of zinc ions, inhibiting the formation of sharp zinc dendrites from the root of the reaction, achieving uniform zinc deposition, and eliminating the external environmental conditions for zinc dendrite formation.
[0035] Furthermore, by constructing a SnO2-ZrO2 composite zinc-loving coating on the surface of the NP co-doped carbon felt, key issues such as uneven zinc deposition, dendrite growth, and functional layer failure and shedding are further addressed, achieving a secondary enhancement of electrode zinc affinity and long-cycle stability. Moreover, the NP co-doping and SnO2-ZrO2 zinc-loving layer work together to change zinc deposition from concentrated growth at the tip to uniform nucleation at multiple sites and controllable filling along the framework, thereby simultaneously suppressing dendrites / dead zinc, mitigating hydrogen desorption side reactions, reducing polarization, and improving cycle stability.
[0036] Preferably, in step S02, the concentration of ammonium dihydrogen phosphate in the precursor solution is 0.25~0.3mol / L; the mass ratio of chitin to ammonium dihydrogen phosphate in the precursor solution is (1~5):1.
[0037] Preferably, in step S02, the mass ratio of chitin contained in the precursor liquid to the pretreated carbon felt is (1~25):1.
[0038] Preferably, in step S02, the inert atmosphere is one of the following: nitrogen, argon, helium, or neon; the heating rate to 450~550℃ is 2~6℃ / min; and the holding time for calcination is 2~6h.
[0039] Preferably, in step S02, the ultrasonic impregnation time is 0.3~0.7h; the vacuum drying temperature is 50~90℃, and the vacuum drying time is 5~9h.
[0040] Preferably, in step S03, the concentration of ZrOCl2·8H2O in the mixed solution is 0.1~0.2 mol / L; the mass ratio of SnCl4·5H2O to ZrOCl2·8H2O in the mixed solution is (1~5):1; the weight of citric acid added to the mixed solution is 5~10% of the total weight of SnCl4·5H2O and ZrOCl2·8H2O; and the volume fraction of ethanol in the ethanol aqueous solution used in the mixed solution is 50~85%.
[0041] Preferably, in step S03, the mass ratio of ZrOCl2·8H2O in the mixed solution to NP co-doped carbon felt is (8.8~9.2):1.
[0042] Preferably, in step S03, the oxygen-containing atmosphere includes air; the heating rate to 300~400℃ is 1~5℃ / min; and the holding time for calcination is 1~5h.
[0043] Preferably, in step S03, the ultrasonic impregnation time is 0.3~0.7h; the vacuum drying temperature is 50~90℃, and the vacuum drying time is 5~9h.
[0044] Further, the method of step S01 is as follows: the polyacrylonitrile-based carbon felt is washed sequentially with anhydrous acetone and anhydrous ethanol, then rinsed with deionized water; then placed in dilute nitric acid, kept at 70~80℃ for heat treatment, then rinsed with deionized water until neutral, and dried to obtain pretreated carbon felt.
[0045] Preferably, in step S01, the volume of anhydrous acetone is 2 to 5 times the volume of polyacrylonitrile-based carbon felt; the volume of anhydrous ethanol is 2 to 5 times the volume of polyacrylonitrile-based carbon felt; and the volume of deionized water is 2 to 5 times the volume of polyacrylonitrile-based carbon felt.
[0046] Preferably, in step S01, the concentration of dilute nitric acid is 1.8~2.3 mol / L; the volume of dilute nitric acid is 2~5 times the volume of polyacrylonitrile-based carbon felt.
[0047] Preferably, in step S01, the heat preservation treatment at 70~80℃ takes 1~2 hours.
[0048] Secondly, the present invention also provides an NP co-doped-zincophilic layer composite modified zinc-bromine flow battery carbon felt prepared by the aforementioned preparation method, comprising a carbon felt substrate, an NP co-doped layer and a zincophilic coating; wherein the NP co-doped layer is coated on the carbon fiber surface of the carbon felt substrate, and the zincophilic coating covers the surface of the NP co-doped layer.
[0049] Thirdly, the present invention also provides the application of the NP co-doped-zincophilic layer composite modified zinc-bromine flow battery carbon felt in the preparation of the negative electrode of a zinc-bromine flow battery.
[0050] To enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described below in conjunction with some specific embodiments.
[0051] In subsequent embodiments, the pretreated carbon felt used was prepared using the following method: After cutting the polyacrylonitrile (PAN)-based carbon felt into the required size, it was ultrasonically cleaned with acetone and anhydrous ethanol at room temperature for 30 minutes to remove the surface organic sizing agent and processing oil. Then it was rinsed with deionized water. Subsequently, it was immersed in a 2 mol / L dilute nitric acid aqueous solution and treated in a water bath at 80°C for 1.5 hours. After that, it was taken out and repeatedly rinsed with deionized water until pH=7. Finally, it was vacuum dried at 80°C for 8 hours to obtain the pretreated carbon felt.
[0052] During the above process, the carbon felt is completely immersed in acetone, anhydrous ethanol, dilute nitric acid aqueous solution, and deionized water, with the volume of each solution controlled to be 4 times the volume of the carbon felt, and the liquid level at least 2 cm above the upper surface of the carbon felt.
[0053] Example 1 This embodiment provides a method for preparing NP co-doped-zincophilic layer composite modified carbon felt for zinc-bromine flow batteries, specifically as follows: (1) NP co-doping modification: Chitin and ammonium dihydrogen phosphate were mixed at a mass ratio of 3:1 and dissolved in deionized water. The concentration of ammonium dihydrogen phosphate was controlled at 0.284 mol / L to obtain a precursor solution. The pretreated carbon felt was placed in the precursor solution, and the mass ratio of chitin in the precursor solution to the pretreated carbon felt was controlled at 7.5:1. The carbon felt was ultrasonically impregnated for 0.5 h to make the precursor uniformly adsorbed on the surface of the carbon felt. It was vacuum dried at 80℃ for 8 h, and then transferred to a tube furnace. Nitrogen gas was introduced and the temperature was raised to 500℃ at a heating rate of 5℃ / min. The temperature was kept warm and calcined for 3.5 h. The temperature was then cooled to room temperature to obtain NP co-doped carbon felt. (2) Preparation of zinc-loving coating: SnCl4·5H2O and ZrOCl2·8H2O were mixed and dissolved in an ethanol aqueous solution (ethanol volume fraction 50%) at a mass ratio of 4:1. The concentration of ZrOCl2·8H2O was controlled to be 0.155mol / L. Citric acid, accounting for 6% of the total mass of SnCl4·5H2O and ZrOCl2·8H2O, was added as a dispersant to obtain a mixed solution. The NP co-doped carbon felt was placed in the mixed solvent, and the mass ratio of ZrOCl2·8H2O to NP co-doped carbon felt in the mixed solution was controlled to be 9:1. The solution was ultrasonically impregnated for 0.5h, removed and vacuum dried at 80℃ for 8h. Then it was transferred to a tube furnace and heated to 320℃ at a heating rate of 2℃ / min under an air atmosphere. The temperature was held for calcination for 3.2h and cooled to room temperature to obtain the NP co-doped-zinc-loving layer composite modified zinc bromine flow battery carbon felt.
[0054] This embodiment also provides an NP co-doped zinc-loving layer composite modified zinc-bromine flow battery carbon felt prepared using the aforementioned method.
[0055] Example 2 This embodiment provides a method for preparing NP co-doped-zincophilic layer composite modified carbon felt for zinc-bromine flow batteries, specifically as follows: (1) NP co-doping modification: Chitin and ammonium dihydrogen phosphate were mixed at a mass ratio of 1:1 and dissolved in deionized water. The concentration of ammonium dihydrogen phosphate was controlled at 0.284 mol / L to obtain a precursor solution. The pretreated carbon felt was placed in the precursor solution, and the mass ratio of chitin in the precursor solution to the pretreated carbon felt was controlled at 2.5:1. The carbon felt was ultrasonically impregnated for 0.5 h to make the precursor uniformly adsorbed on the surface of the carbon felt. It was vacuum dried at 90℃ for 9 h, and then transferred to a tube furnace. Argon gas was introduced and the temperature was raised to 550℃ at a heating rate of 6℃ / min. The temperature was kept warm and calcined for 3 h. The temperature was then cooled to room temperature to obtain NP co-doped carbon felt. (2) Preparation of zinc-loving coating: SnCl4·5H2O and ZrOCl2·8H2O were mixed and dissolved in an ethanol aqueous solution (ethanol volume fraction 83.3%) at a mass ratio of 1:1. The concentration of ZrOCl2·8H2O was controlled to be 0.155mol / L. Citric acid, accounting for 10% of the total mass of SnCl4·5H2O and ZrOCl2·8H2O, was added as a dispersant to obtain a mixed solution. The NP co-doped carbon felt was placed in the mixed solvent, and the mass ratio of ZrOCl2·8H2O to NP co-doped carbon felt in the mixed solution was controlled to be 9:1. The solution was ultrasonically impregnated for 0.5h, removed and vacuum dried at 90℃ for 9h. Then it was transferred to a tube furnace and heated to 400℃ at a heating rate of 5℃ / min under an air atmosphere. The temperature was held for 2.2h and then cooled to room temperature to obtain the NP co-doped-zinc-loving layer composite modified zinc bromine flow battery carbon felt.
[0056] This embodiment also provides an NP co-doped zinc-loving layer composite modified zinc-bromine flow battery carbon felt prepared using the aforementioned method.
[0057] Example 3 This embodiment provides a method for preparing NP co-doped-zincophilic layer composite modified carbon felt for zinc-bromine flow batteries, specifically as follows: (1) NP co-doping modification: Chitin and ammonium dihydrogen phosphate were mixed at a mass ratio of 5:1 and dissolved in deionized water. The concentration of ammonium dihydrogen phosphate was controlled at 0.284 mol / L to obtain a precursor solution. The pretreated carbon felt was placed in the precursor solution, and the mass ratio of chitin in the precursor solution to the pretreated carbon felt was controlled at 12.5:1. The carbon felt was ultrasonically impregnated for 0.3 h to make the precursor uniformly adsorbed on the surface of the carbon felt. It was vacuum dried at 80℃ for 8 h, and then transferred to a tube furnace. Helium was introduced and the temperature was raised to 450℃ at a heating rate of 2℃ / min. The temperature was kept warm and calcined for 5.5 h. The carbon felt was cooled to room temperature to obtain NP co-doped carbon felt. (2) Preparation of zinc-loving coating: SnCl4·5H2O and ZrOCl2·8H2O were mixed and dissolved in an ethanol aqueous solution (ethanol volume fraction 80%) at a mass ratio of 5:1. The concentration of ZrOCl2·8H2O was controlled to be 0.155mol / L. Citric acid, accounting for 8% of the total mass of SnCl4·5H2O and ZrOCl2·8H2O, was added as a dispersant to obtain a mixed solution. The NP co-doped carbon felt was placed in the mixed solvent. The mass ratio of ZrOCl2·8H2O to NP co-doped carbon felt in the mixed solution was controlled to be 9:1. The solution was ultrasonically impregnated for 0.3h. After removal, it was vacuum dried at 80℃ for 8h. Then it was transferred to a tube furnace and heated to 300℃ at a heating rate of 1℃ / min under an air atmosphere. The temperature was held for 4.5h and then cooled to room temperature to obtain the NP co-doped-zinc-loving layer composite modified zinc bromine flow battery carbon felt.
[0058] This embodiment also provides an NP co-doped zinc-loving layer composite modified zinc-bromine flow battery carbon felt prepared using the aforementioned method.
[0059] Example 4 This embodiment provides a method for preparing NP co-doped-zincophilic layer composite modified carbon felt for zinc-bromine flow batteries, specifically as follows: (1) NP co-doping modification: Chitin and ammonium dihydrogen phosphate were mixed at a mass ratio of 2:1 and dissolved in deionized water. The concentration of ammonium dihydrogen phosphate was controlled at 0.284 mol / L to obtain a precursor solution. The pretreated carbon felt was placed in the precursor solution, and the mass ratio of chitin in the precursor solution to the pretreated carbon felt was controlled at 2.5:1. The carbon felt was ultrasonically impregnated for 0.6 h to make the precursor uniformly adsorbed on the surface of the carbon felt. It was vacuum dried at 80℃ for 8 h, and then transferred to a tube furnace. Neon gas was introduced and the temperature was raised to 475℃ at a heating rate of 3℃ / min. The temperature was kept warm and calcined for 5 h. The carbon felt was cooled to room temperature to obtain NP co-doped carbon felt. (2) Preparation of zinc-loving coating: SnCl4·5H2O and ZrOCl2·8H2O were mixed and dissolved in an ethanol aqueous solution (ethanol volume fraction 75%) at a mass ratio of 3:1. The concentration of ZrOCl2·8H2O was controlled to be 0.155mol / L. Citric acid, accounting for 7% of the total mass of SnCl4·5H2O and ZrOCl2·8H2O, was added as a dispersant to obtain a mixed solution. The NP co-doped carbon felt was placed in the mixed solvent, and the mass ratio of ZrOCl2·8H2O to NP co-doped carbon felt in the mixed solution was controlled to be 9:1. The solution was ultrasonically impregnated for 0.6h, and then vacuum dried at 80℃ for 8h. Then it was transferred to a tube furnace and heated to 340℃ at a heating rate of 3℃ / min under an air atmosphere. The temperature was kept at 3℃ / min for 3h and then cooled to room temperature to obtain the NP co-doped-zinc-loving layer composite modified zinc bromine flow battery carbon felt.
[0060] This embodiment also provides an NP co-doped zinc-loving layer composite modified zinc-bromine flow battery carbon felt prepared using the aforementioned method.
[0061] Example 5 This embodiment provides a method for preparing NP co-doped-zincophilic layer composite modified carbon felt for zinc-bromine flow batteries, specifically as follows: (1) NP co-doping modification: Chitin and ammonium dihydrogen phosphate were mixed at a mass ratio of 4:1 and dissolved in deionized water. The concentration of ammonium dihydrogen phosphate was controlled at 0.284 mol / L to obtain a precursor solution. The pretreated carbon felt was placed in the precursor solution, and the mass ratio of chitin in the precursor solution to the pretreated carbon felt was controlled at 10:1. The carbon felt was ultrasonically impregnated for 0.4 h to make the precursor uniformly adsorbed on the surface of the carbon felt. It was vacuum dried at 70℃ for 7 h, and then transferred to a tube furnace. Nitrogen gas was introduced and the temperature was raised to 525℃ at a heating rate of 4℃ / min. The temperature was kept warm and calcined for 2.5 h. The temperature was then cooled to room temperature to obtain NP co-doped carbon felt. (2) Preparation of zinc-loving coating: SnCl4·5H2O and ZrOCl2·8H2O were mixed and dissolved in an ethanol aqueous solution (ethanol volume fraction 66.7%) at a mass ratio of 2:1. The concentration of ZrOCl2·8H2O was controlled to be 0.155mol / L. Citric acid, accounting for 8% of the total mass of SnCl4·5H2O and ZrOCl2·8H2O, was added as a dispersant to obtain a mixed solution. The NP co-doped carbon felt was placed in the mixed solvent, and the mass ratio of ZrOCl2·8H2O to NP co-doped carbon felt in the mixed solution was controlled to be 9:1. The solution was ultrasonically impregnated for 0.4h, removed and vacuum dried at 70℃ for 7h. Then it was transferred to a tube furnace and heated to 380℃ at a heating rate of 4℃ / min under an air atmosphere. The temperature was held for 2.5h and then cooled to room temperature to obtain the NP co-doped-zinc-loving layer composite modified zinc bromine flow battery carbon felt.
[0062] This embodiment also provides an NP co-doped zinc-loving layer composite modified zinc-bromine flow battery carbon felt prepared using the aforementioned method.
[0063] Comparative Example 1 Comparative Example 1 uses the technical solution of Example 1. The difference from Example 1 is that in the preparation of the zinc-loving coating, the addition of SnCl4·5H2O is omitted in the mixed solution; correspondingly, the weight of citric acid added is 6% of the weight of ZrOCl2·8H2O. Other operations and process parameters are the same as in Example 1.
[0064] Comparative Example 2 Comparative Example 2 uses the technical solution of Example 1. The difference from Example 1 is that in the NP co-doping modification, ammonium dihydrogen phosphate is omitted from the precursor solution. Instead, chitosan of the same mass as in Example 1 is dispersed in an equal volume of deionized water to form the precursor solution. Other operations and process parameters are the same as in Example 1.
[0065] Electrochemical performance tests were conducted on zinc-bromine flow batteries assembled using the composite modified carbon felts from Examples 1-5 and Comparative Examples 1-2, respectively. In each zinc-bromine flow battery, the composite modified carbon felt prepared in each example and comparative example served as the negative electrode; the pretreated carbon felt used in each example and comparative example served as the positive electrode; a microporous filter membrane served as the separator; the electrolytes for both the positive and negative electrodes consisted of 2 mol / L zinc bromide, 3 mol / L potassium chloride, 0.2 mol / L tetramethylammonium bromide, and 0.2 mol / L tetrabutylammonium bromide; the effective area of the carbon felts used as both the positive and negative electrodes was 3 cm × 3 cm.
[0066] The electrochemical performance of the zinc-bromine flow battery was tested using a constant current charge-discharge mode. During the test, the electrolyte flow rate was controlled at 35 mL / min, initially at 60 mA / cm². 2 Constant current charging for 40 minutes (charge area specific capacity of 40mAh / cm²) 2 The battery was then discharged at a constant current until the voltage reached 0.6V. Based on the battery charge-discharge curves, the electrochemical performance indicators, such as coulombic efficiency (CE), voltage efficiency (VE), and energy efficiency (EE), were calculated. The electrochemical performance results of each zinc-bromine flow battery in the second charge-discharge cycle are shown in Table 1.
[0067] Table 1. Summary of electrochemical performance of each embodiment and comparative example in cycle 2.
[0068] As shown in Table 1, the coulombic efficiency, voltage efficiency, and energy efficiency of the zinc-bromine flow battery using the composite modified carbon felt obtained in Examples 1-5 as the negative electrode are all superior to those of the zinc-bromine flow battery using the composite modified carbon felt obtained in Comparative Examples 1-2 as the negative electrode. This indicates that the present invention can significantly improve the electrochemical performance of the carbon felt by performing NP co-doping modification and composite zincophilic coating on the carbon felt surface. Among all the examples, Example 1, carried out with optimal process parameters, exhibits the best overall performance, with all three efficiency parameters reaching the highest level. With the changes in the process parameters used in the examples, compared with Example 1, the three key indicators of coulombic efficiency, voltage efficiency, and energy efficiency in Examples 2-5 show a decreasing trend. The coulombic efficiency, voltage efficiency, and energy efficiency of Example 1 are 98.9%, 84.5%, and 83.6%, respectively; while the coulombic efficiency, voltage efficiency, and energy efficiency of Example 5 are 96.3%, 83.3%, and 80.3%, respectively. This suggests that optimizing the combination of various process parameters, such as the mass ratio of chitin to ammonium dihydrogen phosphate and the mass ratio of SnCl4·5H2O to ZrOCl2·8H2O, is necessary to better achieve the effect of NP co-doped + SnO2-ZrO2 zinc-loving coating loaded modified carbon felt, thereby significantly improving the electrochemical performance of zinc-bromine flow batteries.
[0069] With the same charging capacity, the higher the ratio of the amount of electricity output during discharge to the amount of electricity input during charging, the higher the coulombic efficiency. The coulombic efficiencies of Examples 1-5 are greater than 96%, while the coulombic efficiencies of Comparative Examples 1-2 do not exceed 92.5%. This indicates that the synergistic effect of NP co-doping and the SnO2-ZrO2 zinc-loving coating significantly improves the coulombic efficiency. The introduced SnO2-ZrO2 component has excellent zinc-loving properties, which can effectively reduce the overpotential of zinc nucleation and increase the density of surface active sites, thereby promoting more reversible insertion and extraction of charges; the strong interfacial interaction between the NP co-doped substrate and the zinc-loving coating can induce uniform zinc deposition / exfoliation behavior, inhibit the random growth of zinc dendrites, and thus construct a flat and dense zinc deposition layer.
[0070] Voltage efficiency refers to the ratio of the average operating voltage of a battery during discharge to the average operating voltage during charging. It reflects the cost the battery incurs to overcome internal resistance during charge-discharge cycles. The voltage efficiencies of Examples 1-5 are greater than 83%, while the voltage efficiencies of Comparative Examples 1-2 are less than 80%. This indicates that the zinc-bromine flow batteries using the carbon felt obtained in Examples 1-5 as the negative electrode have lower polarization and smaller voltage loss. Analysis shows that this is because the introduction of NP co-doping and the SnO2-ZrO2 zincophilic coating significantly improves the voltage efficiency of the system: the SnO2-ZrO2 component effectively reduces the nucleation overpotential of zinc deposition, thus reducing electrochemical polarization during charging; simultaneously, the fast ion / electron channels constructed by NP heteroatoms optimize reaction kinetics and suppress ohmic polarization caused by dendrite growth. The synergistic effect of these two factors results in a more compact charge-discharge curve, thereby significantly reducing ineffective energy consumption during cycling.
[0071] Energy efficiency refers to the ratio of the actual energy output by a battery during discharge to the total energy input during charging. Examples 1-5 exhibit energy efficiencies greater than 80%, while Comparative Examples 1-2 have energy efficiencies not exceeding 74%. The electrodes modified with NP co-doping and the SnO2-ZrO2 zinc-loving coating demonstrate significantly enhanced energy efficiency. This improvement is mainly attributed to two aspects: First, the excellent zinc-loving properties of the SnO2-ZrO2 composition effectively reduce the overpotential for zinc nucleation, suppressing dendrite growth and the accumulation of dead zinc, thereby significantly improving the coulombic efficiency of the system; second, NP co-doping introduces abundant active sites, optimizing the charge transfer kinetics at the electrode / electrolyte interface and effectively alleviating voltage polarization during charge and discharge. This synergistic mechanism of low-barrier nucleation and fast reaction kinetics minimizes ineffective energy consumption during charge-discharge cycles, endowing the modified electrodes with excellent energy conversion efficiency.
[0072] Comparing Example 1 and Comparative Example 1 (NP co-doping + single ZrO2 coating), it can be seen that the SnO2-ZrO2 composite coating formed by introducing a tin source in Example 1 exhibits superior reaction kinetics and deposition uniformity in electrochemical performance. SnO2 itself is a semiconductor, and when it forms a composite coating with ZrO2, their band structures overlap, which facilitates smooth electron movement and significantly reduces the charge transfer resistance of the electrode. SnO2 has an extremely excellent affinity for zinc atoms, serving as a highly efficient anchoring point to guide zinc ions to deposit uniformly on the carbon fiber surface, effectively suppressing the rampant growth of zinc dendrites. ZrO2 is an insulator; although the carbon felt substrate is conductive, the pure ZrO2 coating covering its surface hinders the transfer of electrons to the electrolyte. This leads to an increase in polarization voltage during charging and discharging, resulting in significantly lower voltage and energy efficiency compared to Example 1. The main functions of ZrO2 are corrosion resistance and structural support; its affinity for zinc is far less than that of SnO2. Without the guidance of Sn, zinc ions are more likely to randomly accumulate in areas of concentrated electric field, leading to uneven zinc deposition. After long-term cycling, dead zinc or dendrites that pierce the diaphragm are more likely to appear. Due to the insulating properties of the ZrO2 coating, the active sites on the electrode surface are easily passivated by polarization as the number of cycles increases, resulting in a much faster performance degradation under high current than in Example 1.
[0073] Comparing Example 1 and Comparative Example 2, it can be seen that Example 1 (NP co-doping + zinc-loving coating), thanks to the introduction of phosphorus, exhibits significantly better electrochemical performance than Comparative Example 2 (N-doping only + zinc-loving coating). Specifically, NP co-doping, through the synergistic effect of N and P atoms, constructs richer defect structures and active sites, significantly enhancing the zinc affinity and Zn content of the carbon felt surface. 2+ The adsorption capacity effectively reduces the zinc nucleation overpotential and guides uniform deposition, thereby significantly improving rate performance and cycling stability (suppressing dendrites and dead zinc). Simultaneously, the introduction of phosphorus (P) enhances interfacial interactions, strengthens the adhesion between the coating and the substrate, and prevents the shedding of active materials during long cycles. In contrast, Comparative Example 2, lacking the synergistic effect of P, exhibits decreased active site density, ion adsorption kinetics, and interfacial stability, ultimately resulting in inferior capacity, coulombic efficiency, and long-term cycling performance compared to the composite material of Example 1.
[0074] Figure 1 The constant current charge-discharge curves for electrochemical performance testing are shown for the NP co-doped-zincophilic layer composite modified carbon felt of the zinc-bromine flow battery in Example 1 and the composite modified carbon felt of Comparative Example 1, respectively, used as the negative electrodes of the zinc-bromine flow battery. As can be seen from the figures, the difference between Comparative Example 1 and Example 1 is that, after NP co-doping, SnO2 was not loaded onto the carbon felt in Comparative Example 1. During the electrochemical performance testing, the electrolyte flowed at 35 mL / min, and the current was 60 mA / cm². 2Constant current charging for 40 minutes (charge area specific capacity of 40mAh / cm²) 2 Then, it was discharged at a constant current until the voltage reached 0.6V. By comparing the charge-discharge curves, it can be seen that Example 1 exhibits a significant electrochemical performance advantage compared to Comparative Example 1: firstly, in terms of discharge capacity, the capacity of Example 1 is extended to nearly 35 mAh / cm³. 2 It far exceeds the 30mAh / cm³ of Comparative Example 1. 2 This indicates that it greatly improves the zinc deposition rate and the utilization rate of active materials. Secondly, in terms of energy efficiency, the charging platform voltage of Example 1 is significantly lower than that of Comparative Example 1, and the discharge platform is more stable, indicating that the modified layer effectively reduces side reactions such as hydrogen evolution and reduces electrochemical polarization. Finally, in terms of reaction kinetics, the voltage curve of Example 1 is flat in the high capacity range, without the sharp voltage cliff at the end of Comparative Example 1, proving that the electrode has good resistance to concentration polarization and high rate performance, and the overall structural stability is better.
[0075] Figure 2 and Figure 3 Cyclic performance curves of the zinc-bromine flow battery using the NP co-doped-zincophilic layer composite modified carbon felt of Example 1 and the composite modified carbon felt of Comparative Example 1 as the negative electrode are shown. The comparison reveals that the composite coating constructed with SnO2 in Example 1 exhibits significant advantages in solving the failure problem of zinc-based batteries. The coulombic efficiency of Example 1 remained stable at nearly 98%, and the energy efficiency also remained stable at around 82%. This is attributed to the synergistic effect of the two components effectively suppressing zinc dendrite growth and interfacial impedance increase, ensuring excellent reaction reversibility. In contrast, Comparative Example 1 (NP co-doped + single ZrO2) experienced a severe efficiency drop in the later stages of cycling, with the coulombic efficiency plummeting from over 90% initially to around 70%. This exposes a fatal flaw in the single ZrO2 coating during long-term cycling: insufficient mechanical strength or easy collapse of the ionic conductive network, leading to uncontrolled zinc deposition, the formation of loose dendrites, and subsequent detachment, which in turn triggers severe dead zinc accumulation and hydrogen evolution side reactions. Regarding energy efficiency, Comparative Example 1 not only exhibited a low initial energy efficiency but also experienced severe fluctuations. These fluctuations reflected poor contact between the single ZrO2 coating and the electrolyte, leading to irregular fluctuations in interfacial impedance during cycling and resulting in significant polarization losses. The single coating in Comparative Example 1 showed a precipitous drop in both coulombic and energy efficiencies during long-term cycling, revealing its significant shortcomings in resistance to side reactions and structural stability. This comparison directly demonstrates that the dual-coating design successfully overcomes the core challenges of traditional electrode lifespan degradation and efficiency fluctuations, achieving ultra-high stability during long-term battery operation.
[0076] Figure 4The X-ray diffraction (XRD) patterns are shown for the NP co-doped zinc-loving layer composite modified zinc-bromine flow battery carbon felt of Example 1 of the present invention and the pretreated carbon felt used therein. It can be seen that, compared with the pretreated carbon felt, the composite modified zinc-bromine flow battery carbon felt of Example 1 shows SnO2 (101), (200) and (211) diffraction peaks at approximately 33.9°, 37.9° and 51.8°, and ZrO2 (101) and (111) diffraction peaks at approximately 30.3° and 31.5°. This indicates that Example 1 successfully loaded SnO2 and ZrO2 onto the carbon felt. In nitrogen-phosphorus co-doped carbon felt, the doped N and P atoms do not form a long-range ordered crystal structure, and no characteristic diffraction peaks belonging to elemental N or P appear. However, the main peak is located at 24.5~25.5°; there are no obvious sharp new peaks, and the peak width of the main peak narrows, indicating that N and P elements have been attached. Further comparison of the X-ray diffraction (XRD) patterns of the NP co-doped-zincophilic layer composite modified zinc-bromine flow battery carbon felt of Example 1 and the pretreated carbon felt used therein shows that, except for the diffraction peaks of SnO2 and ZrO2, the other diffraction peaks are basically the same. This result indicates that the modification process of Example 1 only loads SnO2 and ZrO2 on the surface of the carbon felt; this modification process does not destroy the crystal structure of the carbon felt, and while achieving SnO2 and ZrO2 loading, it completely preserves the original crystal phase characteristics of the carbon felt.
[0077] Figure 5 and Figure 6 The images show scanning electron microscope (SEM) images of the NP co-doped-zincophilic layer composite modified zinc-bromine flow battery carbon felt of Example 1 and the composite modified carbon felt of Comparative Example 1, respectively. Figure 5 It can be clearly seen that the SnO2 and ZrO2 modified carbon felt prepared in Example 1 has many particles on its carbon fibers. These particles are finer and more uniform, have a stronger matte finish, more continuous coverage, and better pore structure. Figure 6 In Comparative Example 1, the carbon fibers of the composite modified carbon felt (NP co-doped + single ZrO2 modified) exhibited large particles, heavy agglomeration, uneven coverage, a large amount of exposed carbon, and easy agglomeration at the intersections.
[0078] Figure 7 The electron image is obtained during energy-dispersive X-ray spectroscopy analysis of the NP co-doped-zincophilic layer composite modified zinc-bromine flow battery carbon felt of Example 1 of this invention. Figure 8 for Figure 7 The energy-dispersive X-ray spectra (EDS) of the selected region of satellite 26 show obvious N, P, Sn, and Zr signals. Combined with... Figure 7 , Figure 8 and Figure 4The X-ray diffraction (XRD) pattern of the NP co-doped +SnO2-ZrO2 zinc-loving coating modified carbon felt prepared in Example 1 can confirm... Figure 5 The particles on the carbon fiber are SnO2 and ZrO2. This further illustrates that N, P, SnO2 and ZrO2 were loaded onto the carbon felt using the technical solution of Example 1.
[0079] Unless otherwise stated, all percentages used in this invention are mass percentages.
[0080] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing an NP co-doped-zincophilic layer composite modified carbon felt for zinc-bromine flow batteries, characterized in that, Includes the following steps: Step S01: The carbon felt is washed and dried to obtain pretreated carbon felt; Step S02: Place the pretreated carbon felt in the precursor solution, ultrasonically impregnate it, take it out and dry it; then heat it to 450~550℃ under an inert atmosphere and calcine it to obtain NP co-doped carbon felt. The precursor solution is an aqueous solution of ammonium dihydrogen phosphate in which chitin is dispersed. Step S03: Place the NP co-doped carbon felt in a mixed solution, ultrasonically impregnate it, remove it and dry it; then heat it to 300~400℃ in an oxygen atmosphere and keep it at the temperature for calcination to obtain the NP co-doped-zinc-loving layer composite modified zinc bromine flow battery carbon felt. The mixed solution is an aqueous solution of ethanol containing citric acid, SnCl4·5H2O, and ZrOCl2·8H2O.
2. The method for preparing the NP co-doped-zincophilic layer composite modified zinc-bromine flow battery carbon felt according to claim 1, characterized in that, In step S02, the concentration of ammonium dihydrogen phosphate in the precursor solution is 0.25~0.3mol / L; the mass ratio of chitin to ammonium dihydrogen phosphate in the precursor solution is (1~5):
1.
3. The method for preparing the NP co-doped-zincophilic layer composite modified zinc-bromine flow battery carbon felt according to claim 1, characterized in that, In step S02, the mass ratio of chitin contained in the precursor liquid to the pretreated carbon felt is (1~25):
1.
4. The method for preparing the NP co-doped-zincophilic layer composite modified zinc-bromine flow battery carbon felt according to claim 1, characterized in that, In step S02, the inert atmosphere is one of the following: nitrogen, argon, helium, or neon; The heating rate to 450~550℃ is 2~6℃ / min; The calcination time is 2-6 hours.
5. The method for preparing the NP co-doped-zincophilic layer composite modified zinc-bromine flow battery carbon felt according to claim 1, characterized in that, In step S03, the concentration of ZrOCl2·8H2O in the mixed solution is 0.1~0.2 mol / L; The mass ratio of SnCl4·5H2O to ZrOCl2·8H2O in the mixed solution is (1~5):1; The weight of citric acid added to the mixed solution is 5-10% of the total weight of SnCl4·5H2O and ZrOCl2·8H2O; The volume fraction of ethanol in the aqueous ethanol solution used in the mixed solution is 50-85%.
6. The method for preparing the NP co-doped-zincophilic layer composite modified zinc-bromine flow battery carbon felt according to claim 1, characterized in that, In step S03, the mass ratio of ZrOCl2·8H2O to NP co-doped carbon felt in the mixed solution is (8.8~9.2):
1.
7. The method for preparing the NP co-doped-zincophilic layer composite modified zinc-bromine flow battery carbon felt according to claim 1, characterized in that, In step S03, the oxygen-containing atmosphere includes air; The heating rate to 300~400℃ is 1~5℃ / min; The calcination time is 1-5 hours.
8. The method for preparing the NP co-doped-zincophilic layer composite modified zinc-bromine flow battery carbon felt according to claim 1, characterized in that, The method of step S01 is as follows: the carbon felt is washed sequentially with anhydrous acetone and anhydrous ethanol, then rinsed with deionized water; then placed in dilute nitric acid, kept at 70~80℃ for heat treatment, then rinsed with deionized water until neutral, and dried to obtain pretreated carbon felt.
9. A carbon felt for a zinc-bromine flow battery with NP co-doped zinc-loving layer composite modification, characterized in that, It is prepared by the preparation method according to any one of claims 1-8.
10. A zinc-bromine flow battery, characterized in that, The carbon felt for zinc-bromine flow batteries using the NP co-doped zinc-philic layer composite modification as described in claim 9 is employed.
Citation Information
Patent Citations
Zinc-bromine flow battery negative electrode material, preparation method thereof and zinc-bromine flow battery
CN117832517A
